Technical Assistance to Improve Public Service Delivery in General Administrative Affairs - Sahril; Zaenal Abidin; Kurniawan; Syahiruddin; Sudirman; M. Ahmed (CV. Zabags Qu Publish, 2025)
Public service delivery at the sub-district level plays a pivotal role in realizing responsive, transparent, and accountable governance. However, various challenges such as limited human resources, inadequate documentation systems, and minimal utilization of information technology continue to hinder the effectiveness of administrative services. This study aims to examine the contribution of university students through Field Practice as a form of technical assistance to enhance public service quality in the Office of Pandan Jaya Village. Employing a qualitative approach with a phenomenological strategy, data were collected through participatory observation, semi-structured interviews, and administrative documentation, and were analyzed thematically. The findings reveal four key themes: understanding the public service system, administrative assistance, application of modern administrative principles and service ethics, and institutional synergy between academia and local government. The results demonstrate that students actively functioned as facilitators, innovators, and collaborative partners in accelerating service processes, improving archival systems, and strengthening the institutional capacity of the village office. This study offers a conceptual contribution to the development of collaborative models between higher education and local governance, and practical implications for designing more strategic it programs oriented toward public service reform based on community needs.